A relação entre o goal orientation e o sucesso de projetos com a moderação do exploitation e exploration em organizações baseadas em projetos - Chies, Tawnee Gomes (2021)
Through analysis of both academic and gray literature, it was identified that in order to achieve the project success and prevent failures, the adoption of soft skills is supported, where it can be represented by the theory of goal orientation that identifies people's predisposition to learn or with a focus on performance. A context of PBO (project-based organizations) was added where inherent characteristics such as temporality, singularity and short-term focus make it difficult to manage both learning related to exploration and exploitation; and the results were observed and compared with an POO context (project-oriented organization), which determines project management as an organizational strategy, applying the project to the performance of complex processes, with a future orientation. Thus, this paper has the objective to analyze which predispositions of individuals related to goal orientation can be motivated to obtain the success of the project in its dimensions, considering contexts of exploitation and exploration as a strategic dilemma in PBOs, comparing the results to those of POOs. This dissertation followed the logic of the quantitative approach with data collection through surveys and with data analysis using multiple linear regression. In general, due to the adjusted R2 values presented in the results, the predisposition of individuals to learning orientation significantly benefits the success of projects in the dimensions tested in relation to the team, the client and the long-term benefits of the project. It was also found that the predispositions of the individual represented by the theory of goal orientation benefit the success of the project in the dimension of commercial success, and that, while exploitation enhances a positive relationship between GOPD and the success of the project, exploration enhances a relationship between GOA and the success of the project. Finally, it is suggested that the support of top management, the strategic orientation of the projects and the vision of the future in POOs may explain the most significant results when compared with those of PBOs, in the dimensions of success of impact on the client, business and direct success and preparation for the future.